Analyzing the role of government efficiency on financial development for OECD countries - Aysel Amir; Korhan K. Gökmenoglu (Review of Economic Perspectives, 2020)
This paper fulfills a gap in the existing literature by analyzing the impact of government efficiency and corruption on the financial development of 31 OECD countries for the period 2002 to 2015 inclusively. To ensure robustness in our estimations, we employed several econometrics techniques, included control variables in our models, used several proxies for the variables under investigation, split the data into subgroups based on the degree of democracy, and repeated the analysis for these groups. Obtained findings provide strong evidence that government efficiency has a significant effect on financial development, and the sign of all the control variables are compatible with the a-priory theoretical expectations. The results of this study propose several policy recommendations to enhance financial development such as enhancing social cohesion through education on the use of tax contributions, revising budget procedures to ensure efficient spending of resources and to improve institutional quality, and reducing corruptive pursuits by targeting the informal economy activities and modifying the rule of law.
Keywords: C33; D73; H11; 330; Financial development; government efficiency; OECD countries; panel data